The Public Gossip of Town Topics: The Journal of Society (1885-1937) - Katrin Horn (European Journal of American Studies)
The magazine Town Topics, published in New York City between 1885 and 1937, is best known for its “complicitous gossip pages [which] both condemned and sustained high society” (Knight 47). The specific characteristics and implications of such gossip, however, have yet to be examined. To this end, this essay analyzes how Town Topics: The Journal of Society and specifically its column “Saunterings” addressed its mass audience. Of central concern to this question are the magazine’s treatment of public figures and its anticipation of modern celebrity culture, and the gossip column’s stylistic evocation of conversational tone. Drawing on Michael Warner’s concept of “a public,” this essay outlines how gossip, a private mode of communication, is used within the public sphere to create the impression of intimate exchange. Overall, this article illustrates how Town Topics differentiated itself from traditional newspapers and magazines, which targeted “the public” as a “social totality” (Warner 413). Town Topics, in contrasts, addressed not the public as an independent, pre-existing entity, but as a specific public that was constituted by the act of mass-mediated gossip.